The changes in pore space in humus aggregates of soddy podzolic soils in conditions of multiple freezing and thawing process - E. B. Skvortsova; E. V. Shein; K. A. Romanenko; K. N. Abrosimov; A. V. Yudina; V. V. Klyueva; D. D. Khaidapova; V. V. Rogov (DOKUCHAEV SOIL BULLETIN, 2018)
The paper discuss the literature data on clay mineralogy of vertisols and presents the investigation of clayey soils formed in ultra-continental climate in the Eravna depression (Buryatia). Soils are formed on the watershed and shoulder positions of the local ridge and are underlined by permafrost. Morphological analysis of soils revealed a combination of cryogenic features (permafrost wedges and cracks, cryogenic structure, above permafrost gleyization) and vertic properties (slickensides, wedge-shaped aggregates). According to the morphology, the soils were classified as Dark compact soil or Gleyic Vertisol Glossic Gelistagnic on the shoulder position, and as Chernozem-like weakly compacted cryoturbated soil or Vertic Gleyic Phaeozem Glossic Pachic Clayic Gelistagnic on the watershed where vertic features were weakly expressed. According to physical properties and clay mineralogy, the shrinking-swelling potential of the soil on the watershed is comparable to the soil of the shoulder: almost the same, and in some horizons even higher content of clay (up to 76%), fine clay (up to 54%) and swelling components in the fine clay (